2012
DOI: 10.1530/joe-12-0421
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin regulates gastric emptying in ovariectomized rats

Abstract: Prolongation of gastrointestinal transit resulting in nausea and vomiting in pregnancy (NVP) is the most common phenomenon during the first trimester of pregnancy. Increased human chorionic gonadotropin (hCG) concentration during the first trimester is the most likely cause of NVP. The aim of this study was to investigate the effect of hCG on gastrointestinal transit and plasma concentrations of cholecystokinin (CCK) in ovariectomized (Ovx) rats. I.p. injection of hCG was used to evaluate the dose effect of hC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…By virtue of the higher placental- and birth weights observed, the NVP and NP women have most likely experienced a higher plasma volume expansion than the SF group [ 50 ], increasing their susceptibility to a delayed reset. Furthermore, abnormal levels of both relaxin and hCG have been implicated with gastrointestinal motility and gastric dysrhythmias, which are factors suggested to contribute to NVP [ 1 , 4 , 13 , 44 , 51 ], although with an absence of biomarker data in this study these associations are speculative. The hCG-relaxin dialogue hints at the complex role these hormones have in early pregnancy and future NVP research should consider both hormones when designing studies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…By virtue of the higher placental- and birth weights observed, the NVP and NP women have most likely experienced a higher plasma volume expansion than the SF group [ 50 ], increasing their susceptibility to a delayed reset. Furthermore, abnormal levels of both relaxin and hCG have been implicated with gastrointestinal motility and gastric dysrhythmias, which are factors suggested to contribute to NVP [ 1 , 4 , 13 , 44 , 51 ], although with an absence of biomarker data in this study these associations are speculative. The hCG-relaxin dialogue hints at the complex role these hormones have in early pregnancy and future NVP research should consider both hormones when designing studies.…”
Section: Discussionmentioning
confidence: 84%
“…Both hormones feature prominently during the first weeks of pregnancy and act in tandem, appropriately raising suspicion as to their contribution to NVP [ 42 ]. Currently, hCG is primarily suspected of being responsible for NVP, as the timing of release correlates with the onset of symptoms [ 3 , 43 , 44 ], although relaxin’s timing is near identical [ 42 ]. It is noteworthy that low relaxin levels have been implicated in hypertension and preeclampsia by affecting endothelial vasodilation, and relaxin as a treatment for preeclampsia is currently under research [ 37 , 42 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired gastric function leads to impaired gastric accommodation resulting in antral overload manifesting in postprandial fullness and early satiety 22 . During pregnancy, levels of hormones such as oestrogen, progesterone, human chorionic gonadotropin (HCG), relaxin and motilin change dramatically from baseline and have been shown to affect gastric motor function 23–27 . Patients with pre‐existing FD, especially PDS, may be adversely affected.…”
Section: The Interactions Between Pregnancy and Functional Dyspepsiamentioning
confidence: 99%
“…Several studies have shown that patients with hyperemesis gravidarum have higher hCG levels. In addition, hCG levels are associated with the severity of hyperemesis gravidarum 20 . Human Chorionic Gonadotropin causes hyperemesis gravidarum by affecting the upper gastrointestinal tract or by stimulating thyroid function because hCG has a structure similar to TSH (Thyroid Stimulating Hormone) 21 .…”
Section: Disscussionsmentioning
confidence: 99%